PENGARUH LABELISASI HALAL DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK MAKANAN IMPOR DALAM KEMASAN (Studi Kasus Mahasiswa FEBI Uin Sts Jambi) - Dwi Sinta Anggraini (Pt. Anagata Sembagi Education, 2024)
This study aims to reveal the effect of halal labeling and prices on purchasing decisions for imported food products in packaging (a case study of FEBI UIN STS Jambi students). As a goal, among others, to determine the effect of halal labeling on purchasing decisions of imported food products in packaging, and to determine the effect of prices on purchasing decisions of imported food products in packaging. This research uses a descriptive quantitative approach with questionnaire data collection methods (questionnaires), interviews, and documentation. The population in this study were students of FEBI UIN STS Jambi and samples as research respondents will be taken using non-probability sampling techniques with the Slovin formula of 100 students found at the time of the study. Data obtained in this study were analyzed using multiple linear regression analysis with the SPSS 21 program.The results of this study indicate that the calculated F value of 31.724 is greater than the F table of 3.09, which means that simultaneously there is an influence on the labeling of halal (X1) and price (X2) on the purchase decision for imported food products in packaging. Partially, it can be seen that all independent variables influence the purchasing decision, namely the halal labeling variable (X1) of 7,554 is greater than t table of 1.984 and the price (X2) of 2.074 is greater than the value of t table 1.984. Based on the results seen from the beta coefficient, the variable that most influences the Purchase Decision variable is the Halal Labeling variable which has a beta coefficient of 0.597 which is greater than the beta coefficient of the price variable which is only 0.164.